Multivariate analyses of the volatile components in fresh and dried turnip (Brassica rapa L.) chips via HS-SPME–GC–MS - Xue, You-lin; Han, Hao-ting; Liu, Chun-ju; Gao, Qi; Li, Jia-heng; Zhang, Jia-hui; Li, Da-Jing; Liu, Chun-quan (Journal of food science and technology, 2020)
Turnip is a vegetable that has many health promoting effects. To diversify the usage and increase the consumption of turnip, the effects of hot air drying, infrared drying, explosion puff drying and freeze drying (FD) on the volatiles of turnip chips were studied. The volatiles of fresh turnip and dried turnip chips were isolated by HS-SPME–GC–MS and a total of 67 volatiles were identified. However, the volatiles in turnip chips dried by different methods are quite different. Based on principal component analysis and hierarchical cluster analysis, the volatiles of fresh turnip were distinguished from those of the dried chips and FD was separated from the other drying methods. As the result of orthogonal projection on latent structure-discriminant analysis (OPLS-DA), isothiocyanato-cyclopropane and (2-isothiocyanatoethyl)-benzene were identified as the characteristic volatiles of fresh turnip. While, 2-azido-2,3,3-trimethyl-butane and hexanal were identified as the characteristic volatiles for FD dried chips.